Road and intermodal transport performance: the impact of operational costs and air pollution external costs. (June 2017) - Mostert, M.; Caris, A.; Limbourg, S.
Abstract: The transportation of goods is essential for the economy, but it also contributes to air pollution which, in turn, affects human health. These negative impacts generate additional costs for society that are not necessarily taken into account in public transportation policies and in private transportation decisions of companies and individuals. This leads to inefficient transportation systems where the social equilibrium is not reached. Intermodal transport is promoted by the European Commission to reduce these negative externalities. The objective of this paper is to analyze at a strategic level the effect on modal split between road, intermodal rail and intermodal inland waterway transport of several economic or environmental policies. An intermodal allocation model is applied to the Belgian case in order to identify the modal split changes between the single minimization of costs (operational or health-related external) and the introduction of additional road taxes.